2022
DOI: 10.1177/23779608221127948
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors Associated with Symptomatic Dry Eye in Nurses in Palestine During the COVID-19 Pandemic

Abstract: Introduction Working in closed wards at hospitals during night-time shifts and using electronic health records may raise the risk of dry eye disease in nurses. Objective The purpose of the current study was to assess the prevalence and associated factors of dry eye disease among hospital nurses in the North West Bank, Palestine. Methods A descriptive cross-sectional study. The study included 300 nurses who work at hospitals in the North West Bank, Palestine. The Ocular Surface Disease Index (OSDI) questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…By searching the relevant databases, we retrieved a total of 313 articles [PubMed (n = 88), Cochrane Library (n = 2), Embase (n = 42), Web of Science (n = 181)], and 11 met the criteria [17][18][19][20][21][22][23][24][25][26][27] (Fig 1).…”
Section: Literature Search Results and Basic Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…By searching the relevant databases, we retrieved a total of 313 articles [PubMed (n = 88), Cochrane Library (n = 2), Embase (n = 42), Web of Science (n = 181)], and 11 met the criteria [17][18][19][20][21][22][23][24][25][26][27] (Fig 1).…”
Section: Literature Search Results and Basic Characteristicsmentioning
confidence: 99%
“…Eleven studies with 15692 participants were conducted in eight countries and regions [17][18][19][20][21][22][23][24][25][26][27]. Most of these studies were published in 2022 [17][18][19][20][21][22][23][24]26], and the study populations included school children [18,22,27], university students [19,21,23,24,26], healthcare workers [17,25], and other professionals [20]. All studies used various dry eye questionnaires as diagnostic tools (Table 1), and the quality assessment (Table 2) suggested that the studies were of high quality.…”
Section: Literature Search Results and Basic Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations